2015
DOI: 10.1186/s12884-015-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

A community-based assessment of correlates of facility delivery among HIV-infected women in western Kenya

Abstract: BackgroundChildbirth at health facilities is an important strategy to reduce maternal morbidity and mortality, improve fetal outcomes, and reduce mother-to-child transmission of HIV. Although access to antenatal care in Kenya is high (>90%), less than half of births occur at health facilities. This analysis aims to assess correlates of facility delivery among recently pregnant HIV-infected women participating in a community-based survey, and to determine whether these correlates were unique when compared to HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
22
3
Order By: Relevance
“…Home delivery in this setting was lower compared to Western Kenya and Nairobi/Nyanza regions, which reported estimates of 53% and 31% respectively in the HIV infected populations between 2008 and 2011[25,26]. Our estimate was also lower compared to what has been previously reported in other sSA settings[21,23].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Home delivery in this setting was lower compared to Western Kenya and Nairobi/Nyanza regions, which reported estimates of 53% and 31% respectively in the HIV infected populations between 2008 and 2011[25,26]. Our estimate was also lower compared to what has been previously reported in other sSA settings[21,23].…”
Section: Discussioncontrasting
confidence: 82%
“…Risk factors contributing to home deliveries among HIV infected women are comparable to those in women in general population and included low socioeconomic status, long distance to nearest health facility, HIV related stigma, security concerns when a woman goes into labor at night, low education level, fear of harsh treatment at the health facility, not attending antenatal clinic(ANC), not using antiretroviral drugs(ARVs), not knowing partner’s HIV status, unsatisfactory delivery care at the health facility and high parity[4,5,22,25,26,31]. Cultural factors identified include lack of commitment from husband, a feeling that facility delivery is not necessary if previous births were free of problems, previous successful home birth, encouragement by grandmothers to have a home birth, rapid progression of labor and preference to be assisted by a TBA[4,5,26,31].…”
Section: Introductionmentioning
confidence: 99%
“…Jacobs et al [11] explain that services such as counselling and provision of consumer information on health services could help address barriers related to availability. Availability barriers were expressed in various forms, such as perceiving health facility-based care which was not different from other options/alternatives [78]; being unaware of care, type and nature of services [22, 28, 47, 78–83] and having limited media exposure [22, 79, 84]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies which identified demand-side affordability as a barrier reported primarily on household resources and willingness to pay rather than cash flow within society [22, 23, 25, 26, 31, 32, 34, 3638, 40, 41, 4648, 50, 52, 61, 66–71, 7375, 78, 79, 83, 85112]. Some studies cited reports by pregnant women of being too busy or having no time as reasons for non-use of maternity care services [22, 26, 63, 86, 100, 113, 114], which represent opportunity costs.…”
Section: Resultsmentioning
confidence: 99%
“…Programs offering couples voluntary counseling and testing in the antenatal clinic setting have shown mixed efficacy, with improved infant nevirapine use in Kenya but not in Rwanda or Zambia [16, 33, 34]. Awareness of partner HIV status has also been associated with other beneficial outcomes among women with HIV, such as higher facility delivery rates [35]. In Kenya, HIV-infected pregnant women who reported that their partner had been tested for HIV had lower rates of vertical transmission and infant mortality, but awareness of partner HIV status was not captured [36].…”
Section: Discussionmentioning
confidence: 99%